2021
DOI: 10.1007/s10681-021-02902-z
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation assessment of drought tolerance in maize populations from the Sahara in both shores of the Mediterranean Sea

Abstract: Drought is the main stress for agriculture, and maize (Zea mays L.) germplasm from the Sahara has been identified as potential source of drought tolerance; however, information about adaptation of semitropical maize germplasm from the Sahara to temperate areas has not been reported. Our objective was assessing the adaptation of maize germplasm from Saharan oases as sources of drought tolerance for improving yield and biomass production under drought conditions in temperate environments. A collection of maize p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In addition, Saharan maize may be a great donor of alleles of stress tolerance because of its adaptation to biotic and abiotic stress. In this way, there is a high diversity in Algerian maize that may provide new alleles for drought conditions reported by a few authors in their previous phenotypic [63][64][65][66] and genetic [67][68][69] studies using the collection of some maize populations from a subtropical area in the Algerian Sahara. Furthermore, their high genetic divergence was found in the heterotic patterns study of Cherchali et al [70], who suggested the incorporation of this material in breeding programs.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, Saharan maize may be a great donor of alleles of stress tolerance because of its adaptation to biotic and abiotic stress. In this way, there is a high diversity in Algerian maize that may provide new alleles for drought conditions reported by a few authors in their previous phenotypic [63][64][65][66] and genetic [67][68][69] studies using the collection of some maize populations from a subtropical area in the Algerian Sahara. Furthermore, their high genetic divergence was found in the heterotic patterns study of Cherchali et al [70], who suggested the incorporation of this material in breeding programs.…”
Section: Introductionmentioning
confidence: 97%